Green synthesis of cobalt ferrite: A study of structural and optical properties. (2023) - Dhanda, Neetu; Thakur, Preeti; Thakur, Atul
Abstract: The cobalt ferrite (CoFe2 O4 ) nanoparticles were prepared using green synthesis approach. The structural formation and purity phase were observed by the analysis of the XRD and also it confirms the single phased spinel cubic structure of nanoparticles. The average crystallite size calculated from FWHM of the most intense peak (3 1 1) was found to be 28 nm. The X-ray density (5.30 g/cm 3 ) and lattice constant (8.382 Å) were also calculated from the XRD data. FTIR spectra show two characteristics bands at the octahedral and tetrahedral sites. The Tauc plot of UV–Vis absorbance spectra gives 2.24 eV of band gap energy value. This synthesis process is environmental friendly and can be used for the antimicrobial activity.